Purification and immunoglobulin E epitopes identification of low molecular weight glutenin: an allergen in Chinese wheat - Yanbo Wang; Yihang Tong; Jinru Zhou; Dong Yang; Linglin Fu (Food Science and Human Wellness)
As one of the most important cereals, wheat (Triticum aestivum) has high nutritional value and is widely cultivated in China. However, wheat can cause severe allergic reactions, and a growing number of people are developing allergies to Chinese wheat. Low molecular weight glutenin (LMW-GS), an important allergen in susceptible populations, is responsible for celiac disease and wheat contacts dermatitis. In this study, LMW-GS was highly purified from Chinese wheat (Xiaoyan 6) and further identified and characterized. In addition, 8 peptides were predicted efficiently by 5 immunological tools, among which five peptides showed significant immunoglobulin E (IgE) binding abilities. Two specific epitopes were found to be in the non-conserved region of the amino acid sequence of LMW-GS, which was speculated to be the specific epitope of Chinese wheat. This systematic research of LMW-GS may provide new insights into the prevention of wheat allergy and development of hypoallergenic wheat products.